2019
DOI: 10.21608/ejnf.2019.103469
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response of Broiler Chickens Under Heat Stress Conditions for Some Organic Antioxidant Additives.

Abstract: ne hundred and twenty 1-d old commercial broiler chicks (Cobb) were divided in to four groups with six replicats, to investigate the effect of dietary supplementation with organic chromium (Cr), organic selenium (Se) and Vitamin E (Vit.E) on some physiological and immunological parameters. The first group was the control group, while the second group was fed the basal diet supplemented with organic chromium (0.8 mg/kg diet), the third group was fed the basal diet supplemented with organic selenium (0.3 mg/kg d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…These results are similar to Rashidi et al (2010), who found that vitamin E supplementation improved plasma total protein, albumin and globulin. Also, Gouda et al (2019), who found that supplementation of vitamin E (200 IU/kg diet) increase the total plasma protein and globulin values (P< 0.05) at 42 day old chicks. Moreover, Attia et al (2020) explained the same result.…”
Section: Discussionmentioning
confidence: 96%
“…These results are similar to Rashidi et al (2010), who found that vitamin E supplementation improved plasma total protein, albumin and globulin. Also, Gouda et al (2019), who found that supplementation of vitamin E (200 IU/kg diet) increase the total plasma protein and globulin values (P< 0.05) at 42 day old chicks. Moreover, Attia et al (2020) explained the same result.…”
Section: Discussionmentioning
confidence: 96%